2014
DOI: 10.1002/lt.23890
|View full text |Cite
|
Sign up to set email alerts
|

Surgical site infections after liver retransplantation: Incidence and risk factors

Abstract: Surgical site infections (SSIs) after liver transplantation (LT) are associated with an increased risk of graft loss and death. The incidence of SSIs after LT and their risk factors have been determined for first LT but not for second LT. The importance of reporting the incidence of SSIs risk-stratified by first LT versus second LT is not known. All patients undergoing second LT at a single institution between 2003 and 2011 (n 5 152) were reviewed. The Kaplan-Meier method was used to estimate the cumulative SS… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

1
1
1

Year Published

2015
2015
2024
2024

Publication Types

Select...
4
4

Relationship

0
8

Authors

Journals

citations
Cited by 13 publications
(3 citation statements)
references
References 18 publications
(43 reference statements)
1
1
1
Order By: Relevance
“…Relative to these other studies, our study also involved a higher mean intraoperative red blood cell transfusion volume [ 9 , 16 ]. Furthermore, the MELD/PELD scores in our study were higher than those reported in previous studies [ 8 , 18 ]. These factors cannot be discounted as risk factors for SSI after LDLT because they affected most of the patients examined in this study.…”
Section: Discussioncontrasting
confidence: 95%
“…Relative to these other studies, our study also involved a higher mean intraoperative red blood cell transfusion volume [ 9 , 16 ]. Furthermore, the MELD/PELD scores in our study were higher than those reported in previous studies [ 8 , 18 ]. These factors cannot be discounted as risk factors for SSI after LDLT because they affected most of the patients examined in this study.…”
Section: Discussioncontrasting
confidence: 95%
“…Thus, the higher risk of SSI in these patients is not unexpected. 26 Similar to other studies, we found an increased risk of SSI with posttransplant procedures 9,16 and longer operative times as has been, 4,27,28 which likely reflects increased opportunity for wound contamination, increased inflammation, and delayed healing. There may be some variability in surgical techniques that can potentially influence the rate of SSI.…”
Section: Discussionsupporting
confidence: 88%
“…[4][5][6][7][8] The risk for SSI among liver transplant recipients is heightened by multiple factors, including underlying comorbidities, complex transplant procedures involving the biliary tract, multiple transfusions of packed red blood cells, prolonged operative time, and intense immunosuppression. [4][5][6][7][8][9][10][11][12][13][14] Limited data are available on LTP SSI rates, causal pathogens, and antimicrobial resistance, and most data available are from single centers. In these studies, SSI rates attributed to LTPs were reported to range from 8.8% to 37.8%, and the most common pathogens included Enterobacteriaceae, Acinetobacter baumannii, Pseudomonas aeruginosa, Enterococcus spp., Staphylococcus aureus, and Candida spp.…”
Section: Introductionmentioning
confidence: 99%